Profiling of Oligolignols Reveals Monolignol Coupling Conditions in Lignifying Poplar Xylem - Morreel, Kris (American Society of Plant Biologists, 2004)
Lignin is an aromatic heteropolymer, abundantly present in the walls of secondary thickened cells. Although much research has been devoted to the structure and composition of the polymer to obtain insight into lignin polymerization, the low-molecular weight oligolignol fraction has escaped a detailed characterization. This fraction, in contrast to the rather inaccessible polymer, is a simple and accessible model that reveals details about the coupling of monolignols, an issue that has raised considerable controversy over the past years. We have profiled the methanol-soluble oligolignol fraction of poplar (Populus spp.) xylem, a tissue with extensive lignification. Using liquid chromatography-mass spectrometry, chemical synthesis, and nuclear magnetic resonance, we have elucidated the structures of 38 compounds, most of which were dimers, trimers, and tetramers derived from coniferyl alcohol, sinapyl alcohol, their aldehyde analogs, or vanillin. All structures support the recently challenged random chemical coupling hypothesis for lignin polymerization. Importantly, the structures of two oligomers, each containing a γ-p-hydroxybenzoylated syringyl unit, strongly suggest that sinapyl p-hydroxybenzoate is an authentic precursor for lignin polymerization in poplar.